Respuesta :
(x-6)²-6²+5=0
(x-6)²-36+5=0
(x-6)²-31=0
(x-6)²=31
x-6=√31
x=6±√31
x= 11.57 or x=0.43
(x-6)²-36+5=0
(x-6)²-31=0
(x-6)²=31
x-6=√31
x=6±√31
x= 11.57 or x=0.43
Answer:
[tex]x=6+\sqrt{31}[/tex]
[tex]x=6-\sqrt{31}[/tex]
Step-by-step explanation:
Solve [tex]x^2-12x+5 = 0[/tex] using the completing-the-square method.
Subtract 5 from both sides
[tex]x^2-12x=-5[/tex]
In completing the square method , we take coefficient of middle term and then divide by 2 and square it
12 divide by 2 is 6
6^2 = 36
Add 36 on both sides
[tex]x^2-12x+36=-5+36[/tex]
[tex]x^2-12x+36=31[/tex]
Now we factor the left hand side
[tex](x-6)(x-6)=31[/tex]
[tex](x-6)^2=31[/tex]
Take square root on both sides
[tex]x-6=+-\sqrt{31}[/tex]
Now add 6 on both sides
[tex]x=6+-\sqrt{31}[/tex]
So there are two values for x
[tex]x=6+\sqrt{31}[/tex]
[tex]x=6-\sqrt{31}[/tex]